On Multiple Hypotheses Testing by Informed Statistician for Arbitrarily Varying Object and Application to Source Coding - Haroutunian, Evgueni A.; Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2024)
The matrix of asymptotic interdependencies (reliability-reliability functions) of all possible pairs of the error probability exponents (reliabilities) in testing of multiple statistical hypotheses is studied for arbitrarily varying object with the current states sequence known to the statistician. The case of two hypotheses when state sequences are not known to the decision maker was studied by Fu and Shen, and when decision is founded on the known states sequence was considered by Ahlswede, Haroutunian and Aloyan. In the same way as Fu and Shen we obtain from the main result rate-reliability and reliability-rate functions for arbitrarily varying source coding with side information. An illustrative example is presented.